2018
DOI: 10.1111/aos.13997
|View full text |Cite
|
Sign up to set email alerts
|

How do we evaluate the role of focal/grid photocoagulation in the treatment of diabetic macular edema?

Abstract: Vascular endothelial growth factor inhibitors (anti‐VEGF) have consistently demonstrated efficacy and safety and changed both the aim and perspectives of diabetic macular edema (DME) treatment. Hence, the present and future role of focal/grid laser photocoagulation in DME treatment has been subjected to some debate. However, extensive insight into technical advances in novel laser systems, treatment protocols of anti‐VEGF trials and the functional impact of modern focal/grid photocoagulation is needed to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…However, estimated efficacy in our study was comparable to other trials with anti‐VEGF for DME in regard to VA improvement (Blindbaek et al. ). Furthermore, the percentages of eyes with an improvement in letter score of 10 or more and 15 or more in our study were 40 and 16, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…However, estimated efficacy in our study was comparable to other trials with anti‐VEGF for DME in regard to VA improvement (Blindbaek et al. ). Furthermore, the percentages of eyes with an improvement in letter score of 10 or more and 15 or more in our study were 40 and 16, respectively.…”
Section: Discussionsupporting
confidence: 86%
“… 16 Focal laser photocoagulation is regarded as a classical treatment for DME; however, it leads to a number of serious complications. 23 Data from several clinical trials demonstrated significant beneficial effects of anti-VEGF therapy in the management of DME, while anti-VEGF resistance was associated with poor prognosis of DME management. 24 , 25 Although a variety of scientific advances have been made over the last decade, the pathogenesis of DME remains to be discovered fully.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results are approximately at the same level as previous anti-VEGF trials for DMO in regards to improvement in VA and CRT. 27 Hence, we do not believe that the predictive value of retinal arteriolar oxygen saturation is unique to our population due to differences in response to treatment.…”
Section: Open Accessmentioning
confidence: 84%
“…Also, the number of intravitreal injections between BL and month 12 in this study was fairly low as compared with the most previously conducted studies on anti-VEGF monotherapy for DMO. 27 Hence, we speculate that the difference in need for therapy between groups (A and B) may be more pronounced in other treatment regimens with more frequent intravitreal injections. However, further studies with other treatment strategies, for example, intravitreal aflibercept with and without adjunctive focal/grid laser photocoagulation or treat and extend regimens are warranted to clarify the generalisability of our results.…”
Section: Open Accessmentioning
confidence: 88%